Pengaruh Kualitas Pelayanan Dan Fasilitas Kesehatan Terhadap Kepuasan Pasien Di Puskesmas Trimulyo Kabupaten Pesawaran - M. Ardi Rangga Putra; Berlintina Permatasari (CV. Ulil Albab Corp, 2026)
The purpose of this study is to examine how patient satisfaction at Trimulyo Community Health Center in Pesawaran Regency is impacted by health facilities and service quality. The phenomena of variations in the number of patient visits per month in 2024 serves as the foundation for this investigation. The standard of care given by medical professionals and the accessibility of medical facilities are some of the causes of this variation. This study uses a quantitative approach using a cross-sectional design, probability sampling, and purposive sampling using the criterion of people who have made several visits to Trimulyo Community Health Center. The Slovin formula was used to identify 352 responders in total. The data was analyzed using multiple linear regression analysis, validity tests, reliability tests, and normalcy testing. With a score of 12.592 and a significance of 0.001 less than 0.05, the results demonstrated that patient satisfaction is positively and significantly impacted by service quality. With a value of 11.321 and a significance of 0.001 less than 0.05, health facilities also significantly and favorably affect patient satisfaction. Patient happiness is also greatly impacted by the caliber of healthcare facilities and services. Therefore, in order to increase patient happiness and loyalty, Trimulyo Community Health Center needs to improve the quality of its services and available healthcare facilities.